Three decades of stranding data reveal insights into endangered hawksbill sea turtles in Hawai‘i&dagger - S Brunson; AR Gaos; IK Kelly; KS Van Houtan; Y Swimmer; S Hargrove; GH Balazs; TM Work; TT Jones (Endangered Species Research, 2022)
Hawksbill sea turtles Eretmochelys imbricata inhabiting the Hawaiian Islands are extremely rare and listed as endangered under the US Endangered Species Act. The paucity of data on basic hawksbill ecology continues to hinder effective management of the species. We analyzed stranding data collected between 1984 and 2018 to gain insights into the distribution, demography, and conservation challenges facing hawksbills in Hawai‘i. In doing so, we present a comprehensive description of the population across developmental stages and rank threats that may be impeding their successful recovery. Over the >30 yr data set, we recorded a total of only 111 juvenile and adult hawksbill stranding events. Interactions with nearshore recreational fishing gear were documented for a large proportion (48.6%) of stranding events in the Hawaiian Islands, identifying this as the primary management challenge for the species. Stranding events were biased towards females (female to male sex ratio of 4.8:1.0), which may be indicative of the population as a whole. Even though the majority of hawksbills nest on the islands of Hawai‘i Moloka‘i, and Maui, the greatest number of juvenile to adult strandings was found to be on the island of Oahu (n = 47). Temporal distribution of the majority of adult hawksbill strandings (72.2%) occurred during a 4 mo period between June and September. We discuss these and other findings that help identify future research and conservation efforts to mitigate anthropogenic threats in Hawai‘i for this enigmatic population.